Effect of dexamethasone as an adjuvant to 0.5% levobupivacaine in supraclavicular brachial plexus block for upper extremity surgeries - Hanumansetty, Kartheek; S., Hemalatha; L., Gurudatt C. (International Journal of Research in Medical Sciences, 2017)
Background: The supraclavicular brachial plexus block has proven to be an important, safer and effective alternative to general anaesthesia in surgeries of upper extremity. Primary aim is to study the effect of addition of dexamethasone to levobupivacaine on postoperative analgesia and secondary objectives are to study onset, peak effect and duration of sensory and motor block in brachial plexus blockade in adult patients posted for upper limb surgeries Methods: This prospective randomized clinical study was conducted on 60 patients of age 18 to 60 years posted for upper limb surgeries. They were randomly allocated into two groups of 30. In Control group LS (n=30) received Inj. Levobupivacaine 30ml and Inj. Normal saline 2ml. In Study group LD (n=30) received Inj. Levobupivacaine 30ml and Inj. Dexamethasone 2ml (8mg). Results: Both the groups were demographically comparable. Onset of sensory block and motor block in group LD and in group LS were similar (p>0.05). Mean duration of sensory and motor block in group LD was higher than in group LS (<0.001). Duration of postoperative analgesia was 21.20±3.23 hours in group LD and 10.24±1.57 hours in group LS (p<0.001). Conclusions: Dexamethasone added to levobupivacaine for brachial plexus block prolonged the duration of sensory, motor blockade and postoperative analgesia but did not alter the onset time, peak effect time of sensory and motor blockade.